2013
DOI: 10.1002/jaba.50
|View full text |Cite
|
Sign up to set email alerts
|

Training Adults With an Autism Spectrum Disorder to Conduct Discrete-Trial Training for Young Children With Autism: A Pilot Study

Abstract: We evaluated a behavioral skills training program for adults with autism spectrum disorder and mild or no intellectual disabilities who were interested in learning the skills used by behavior therapists to work with young children with autism and other developmental disabilities. Four adults, aged 21 to 30 years, participated. We trained each individually using verbal and written instructions, modeling, and role play with feedback to teach 2 basic skills to an adult who played the role of a young child with au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
6
22
0
3
Order By: Relevance
“…These findings extend previous work on using BST to teach adults with ASD and no ID to implement behavioral procedures with children with ASD (Lerman et al, , ). Results demonstrated that BST was effective for teaching adults with ASD to implement a form of pivotal response training to improve social engagement of children with ASD within a play context.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These findings extend previous work on using BST to teach adults with ASD and no ID to implement behavioral procedures with children with ASD (Lerman et al, , ). Results demonstrated that BST was effective for teaching adults with ASD to implement a form of pivotal response training to improve social engagement of children with ASD within a play context.…”
Section: Discussionsupporting
confidence: 87%
“…Results demonstrated that BST was effective for teaching adults with ASD to implement a form of pivotal response training to improve social engagement of children with ASD within a play context. The format of the play sessions was less structured than that of the teaching sessions in Lerman et al (, 2015) and was intended to influence the quality of the interactions between the adult and the child (i.e., increase rapport). Results also suggested that training was responsible for changes in a potential simple measure of rapport (proximity of the child to the adult).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barkaia, Stokes & Mikiashvili (2017) successfully trained psychologists to accurately implement the teaching of verbal operants to children with ASD, considering that the training of the professionals was conducted through videoconferences (internet-based training). Lerman et al (2013), Lerman et al (2015) and Shireman, Lerman & Hillman (2017) effectively taught university students with ASD, and without intellectual disabilities, to implement the teaching of basic skills, verbal repertoires, functional play behaviors and how to appropriately manage problem behaviors of children with ASD. Barboza et al (2015) assessed the effects of a variation of the modeling component of the BST.…”
Section: Introductionmentioning
confidence: 99%